PERAN KADER KESEHATAN BAGI PENINGKATAN KESEHATAN LANJUT USIA (LANSIA) DI GEREJA KRISTEN JAWA KRAMAS, KOTA SEMARANG : THE ROLE OF HEALTH CAREERS FOR IMPROVEMENT HEALTH OF THE ELDERLY (ELDERLY) IN JAVA KRAMAS CHRISTIAN CHURCH, SEMARANG CITY - Rahmad Purwanto W; Retno Mratihatami (Jurnal Suara Pengabdian 45, 2022)
This study aims to describe the improvement of elderly health that has been carried out at the Jawa Jawa Kramas Christian Church, Semarang City. Most of the elderly in the church are elderly women who are still active in domestic activities and micro/small economic businesses. Based on the action plan to improve the health of the elderly, it is carried out with integrated data on the elderly, the establishment of elderly institutions, capacity building for health cadres and the implementation of health checks as a promotive step and basic services to the Tembalang Community Health Center. In its development, efforts have brought results and have received appreciation from the church and the surrounding community.